The Cambridge companion to miracles - Twelftree, Graham H. (Cambridge Cambridge University Press, 2011)
"The miracle stories of the founders and saints of the major world religions have much in common. Written by international experts, this Companion provides an authoritative and comparative study of miracles in not only Hinduism, Islam, Buddhism, Christianity and Judaism, but also, indigenous religions. The authors promote a discussion of the problems of miracles in our largely secular culture, and of the value of miracles in religious belief. The miracles of Jesus are also contextualized through chapters on the Hebrew Bible, classical culture to the Romans, Second Temple and early rabbinic Judaism and early Christianity. This book provides students with a scholarly introduction to miracles, which also covers philosophical, medical and historical issues"--Provided by publisher.
Machine generated contents note: Notes on contributors; List of abbreviations; Introduction: miracle in an age of diversity Graham Twelftree; Part I. Fundamental Issues: 1. What is a miracle? David Basinger; 2. Meanings of miracles Robert Larmer; Part II. Miracles in Antiquity and the Middle Ages: 3. The Hebrew Bible / R. Walter L. Moberly; 4. Classical culture to the Romans / Robert Garland; 5. Second Temple and early Rabbinic Judaism / Lidija Novakovic; 6. Jesus / Barry L. Blackburn; 7. Miracle in early Christianity / James Carleton Paget; 8. The Middle Ages/ Benedicta Ward; Part III. Miracles and Major Religions: 9. Traditional religions / Fiona Bowie; 10. Hinduism / Gavin Flood; 11. Islam / David Thomas; 12. Buddhism / Rupert Gethin; 13. Christianity / Ralph Del Colle; 14. Judaism / Kenneth Seeskin; Part IV. Miracle Today: 15. A history of the debates on miracle / Colin Brown; 16. Philosophers on miracle / Michael P. Levine; 17. Patient belief in miraculous healing - positive or negative coping resource / Niels Christian Hvidt.
Keywords: Miracles